The Effect of Organizational Trust on Service Quality in the Public Sector: With Mediating Roles of Participatory Decision-Making and Employees’ Engagement - Araya, Simret Gebretsadik (African Journal of Leadership and Development, 2024)
This study aimed to analyze the effect of organizational trust (OT) on service quality (SQ) via mediation roles of participatory decision making (PDM) and employees’ engagement (EE) in the case of Addis Ababa Water and Sewerage Authority (AAWSA). To that end, the explanatory research design with a mixed methods approach was used. Quantitative data were collected from 75 leaders, 400 employees and 400 customers of AAWSA; whereas qualitative data were collected via interview with purposively selected leaders of same. Data analysis was done using mean, standard deviations and structural equation modeling. Findings revealed that at AAWSA, OT (M=2.83), PDM (M=3.15) and SQ (M=2.69) have moderate levels; whereas EE is high (M=4.20). Besides, the direct effects of OT on SQ (-.15) and EE (.30) are respectively of medium and large size and statistically significant (p<0.05). However, OT’s direct effect on PDM (.03) is small and statistically insignificant (p=.67). Similarly, OT’s indirect effects on SQ via mediations of EE (.01) and PDM (.00) at respective P. values of .61 and .98 are statistically insignificant. Nonetheless, the total effect of OT on SQ via mediations of PDM and EE (-.16) is of a medium size and statistically significant (p=.03). The qualitative findings revealed that the higher level of EE is caused by prevalence of highly controlled work environment and there are other internal and external factors that influence AAWSA’s SQ. Thus, unless AAWSA rethinks the interplay among its OT, PDM, EE and SQ and stretches the potential of its engaged employees to the extent of providing innovative solutions, the city’s residents and development projects will suffer from lack of quality water and sewer services in the near future.